PENGARUH CASHEW NUT SHELL LIQUID (CNSL) TERHADAP MORTALITAS HELOPELTIS ANTONII SIGN PADA BIBIT JAMBU METE - Warsi Rahmat Atmadja; Tri Eko Wahyono (Pusat Penelitian dan Pengembangan Perkebunan, 2006)
Effect of Cashew Nut Shell Liquid (CNSL) to Mortality of Helopeltis antonii Sign on Cashew SeedlingThe effects of CNSL to Helopeltis antonii Sign. on cashew seedling were done in labo-ratory and greenhouse of pest and deaseases division at Research Institute for Spice and Medicinal crops on June until September 2004. The research aimed to study of CNSL influence to H. antonii on cashew seedling. This expe-riment were used two methods, they are topical spray and foliar spray methods. The CNSL treatment that applications to insects with 0.625; 1.25; 2.50 and 5% concentrations and control. The total number of insect were used 10 insects for each treatment of H. antonii adult respectively. The application of cashew seedling used 1.25; 2.50; 5; 10 and 20% concentrations and control. Observation was carried out every day by counting H. antonii mortality level. The research was made with use of Randomized Block Design (RBD) with 5 treatments and 5 replications for topical spray method and 6 treatments and 4 replications for foliar spray method. The research results showed that mor-tality level of insects highest was applied directly to H. antonii in CNSL treatment with 5% concentration was 100% on the 6th days after application, while the application to cashew seedling with 20% concentration on 4, 5, and 6 th days after application, the mortality level of H. antonii were 52.50, 62.50 and 97.50% respectively.